Building-up seaport innovation capabilities: The Port of Gothenburg as a complex logistic system (CoLS) - Scaccianoce, N.; Mendonça, S. (5th INTERNATIONAL CONFERENCE OF THE GOVERNANCE OF ATLANTIC PORTS – Ports and Development, 2017)
.